2013
DOI: 10.1097/acm.0b013e318285800f
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reducing Maximum Shift Lengths to 16 Hours on Internal Medicine Interns’ Educational Opportunities

Abstract: Purpose To evaluate educational experiences of internal medicine interns before and after maximum shift lengths were decreased from 30 hours to 16 hours. Method The authors compared educational experiences of internal medicine interns at Vanderbilt University Medical Center before (2010, 47 interns) and after (2011, 50 interns) duty hour restrictions were implemented in July 2011. The authors compared number of inpatient encounters, breadth of concepts in notes, exposure to five common presenting problems, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 36 publications
0
19
1
Order By: Relevance
“…There were 27 studies included in the final review: 13 (48%) reviewed shift length, [23][24][25][26][27][28][29][30][31][32][33][34][35] 12 (44%) examined Across all of the studies and interventions, the impact of duty hour restrictions most frequently had no impact on patient care (5 of 10, 50%), 23,24,28,41,48 no impact on resident well-being (7 of 17, 41%), 27,34,35,41,44,46,49 and an unfavorable impact on resident education (9 of 14, 64%). 29,30,[33][34][35][36]41,43,46 A minority of studies found a favorable impact on resident well-being (4 of 17, 24%; TABLE 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 27 studies included in the final review: 13 (48%) reviewed shift length, [23][24][25][26][27][28][29][30][31][32][33][34][35] 12 (44%) examined Across all of the studies and interventions, the impact of duty hour restrictions most frequently had no impact on patient care (5 of 10, 50%), 23,24,28,41,48 no impact on resident well-being (7 of 17, 41%), 27,34,35,41,44,46,49 and an unfavorable impact on resident education (9 of 14, 64%). 29,30,[33][34][35][36]41,43,46 A minority of studies found a favorable impact on resident well-being (4 of 17, 24%; TABLE 2).…”
Section: Resultsmentioning
confidence: 99%
“…[23][24][25][26][27][28][29][30][31][32][33][34][35] The length of shifts that were studied ranged from 13 to 36 hours. The populations of interest, and subsequently the study outcomes, were not consistent across all of the studies.…”
Section: Shift Lengthmentioning
confidence: 99%
“…This was chosen because a significant restructuring of resident duty hours occurred in spring 2011 that had the potential to affect all measures studied. 20,21 Finally, we did not collect data on accuracy of the information provided in the handover tool or end-user utilization and were unable to account for effects of these.…”
Section: Resultsmentioning
confidence: 99%
“…Our results are similar to other studies in that reducing census or admitting caps did not substantially change total patient encounters. 23,26 The restructuring changes increased the exposure of residents to an increased number of outpatients, which some educators have made strong arguments in favor of instituting. 27,28 It is important to note that the inpatient WLR approach, by necessitating shifts in overall scheduling, increased patient encounters across a spectrum of care settings (inpatient and ambulatory).…”
Section: Discussionmentioning
confidence: 99%